β- and α-Cell Dysfunctions in Africans With Ketosis-Prone Atypical Diabetes During Near-Normoglycemic Remission - Choukem, Siméon-Pierre; Sobngwi, Eugene; Boudou, Philippe; Fetita, Lila-Sabrina; Porcher, Raphael; Ibrahim, Fidaa; Blondeau, Bertrand; Vexiau, Patrick; Mauvais-Jarvis, Franck; Calvo, Fabien; Gautier, Jean-François (Diabetes care, 2013)
Ketosis-prone atypical diabetes (KPD) is a subtype of diabetes in which the pathophysiology is yet to be unraveled. The aim of this study was to characterize β- and α-cell functions in Africans with KPD during remission. We characterized β- and α-cell functions in Africans with KPD during remission. The cohort comprised 15 sub-Saharan Africans who had been insulin-free for a median of 6 months. Patients in remission were in good glycemic control (near-normoglycemic) and compared with 15 nondiabetic control subjects matched for age, sex, ethnicity, and BMI. Plasma insulin, C-peptide, and glucagon concentrations were measured in response to oral and intravenous glucose and to combined intravenous arginine and glucose. Early insulin secretion was measured during a 75-g oral glucose tolerance test. Insulin secretion rate and glucagon were assessed in response to intravenous glucose ramping. Early insulin secretion and maximal insulin secretion rate were lower in patients compared with control participants. In response to combined arginine and glucose stimulation, maximal insulin response was reduced. Glucagon suppression was also decreased in response to oral and intravenous glucose but not in response to arginine and insulin. Patients with KPD in protracted near-normoglycemic remission have impaired insulin response to oral and intravenous glucose and to arginine, as well as impaired glucagon suppression. Our results suggest that β- and α-cell dysfunctions both contribute to the pathophysiology of KPD.